Catalyst, synthesis method of catalyst, nano carbon material and preparation method of nano carbon material
By introducing carbon quantum dots into the catalyst preparation process, the interaction between the active component iron and the support alumina is enhanced, thereby improving catalytic performance, solving the problems of insufficient catalyst activity and lifetime, and realizing the efficient preparation of nano-carbon materials.
Patent Information
- Application Number
- CN202410665872.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-27
- Publication Date
- 2025-11-28
AI Technical Summary
The catalytic activity and lifespan of catalysts in existing nano-carbon material preparation processes need to be improved.
Carbon quantum dots are introduced into the catalyst preparation process. By mixing an iron source, an aqueous solution of carbon quantum dots, alumina, and ammonia and calcining them, a catalyst supported on alumina is formed, which is then used to react with the carbon source to prepare nano-carbon materials.
It improves the catalytic activity and lifespan of the catalyst, and increases the yield and quality of nano-carbon materials, especially the yield and purity of carbon nanotubes.
Smart Images

Figure BDA0004861070980000101 
Figure BDA0004861070980000111 
Figure BDA0004861070980000131
Abstract
Description
TECHNICAL FIELD
[0001] The present disclosure relates to the field of nanocarbon materials, in particular, to a catalyst and a synthesis method thereof, and a nanocarbon material and a preparation method thereof. BACKGROUND
[0002] Nanocarbon materials, especially carbon nanotubes, as another new type of carbon nanostructure after fullerenes, have caused a great sensation in the scientific community and led to a research boom in nanoscience and nanotechnology. The structure of carbon nanotubes can be imagined as a seamless tubular structure formed by rolling up graphene sheets composed of sp 2 hybridized carbon atoms, which can be divided into single-walled carbon nanotubes and multi-walled carbon nanotubes according to the number of sheet layers.
[0003] The perfect structure of carbon nanotubes makes it have outstanding performance in mechanics, electricity, heat, optics and chemistry. At the same time, due to the particularity of quasi-one-dimensional structure, its performance shows great difference along the axial and radial directions. After twenty years of development, the structure, performance and potential broad application prospect of carbon nanotubes have been fully recognized by scholars.
[0004] As one of the top ten developments in the field of materials in the past fifty years selected by "Materials Today", the discovery of carbon nanotubes not only caused a great sensation in the academic community, but also led to great changes in the industry. After a relatively full understanding of its structure and performance, and the successful realization of batch production of carbon nanotubes using fluidized bed technology in 2001 and 2007, the focus of scholars based on carbon nanotubes gradually shifted from basic research to industrialization. Application exploration is concentrated in the fields of polymer composites, catalyst carriers, adsorption materials, lithium ion batteries or supercapacitors, etc.
[0005] However, the catalytic activity and service life of the catalyst used in the preparation process of nanocarbon materials still need to be further improved. SUMMARY
[0006] The purpose of the present disclosure is to provide a catalyst and a synthesis method thereof, and a nanocarbon material and a preparation method thereof, which have higher catalytic activity and longer service life.
[0007] In order to achieve the above purpose, the first aspect of the present disclosure provides a synthesis method of a catalyst for preparing a nanocarbon material, comprising the following steps:
[0008] S1, mixing an iron source, a carbon quantum dot aqueous solution and aluminum oxide to obtain a raw material mixture;
[0009] S2, mixing and reacting the raw material mixture with ammonia water to obtain a solid product;
[0010] S3, calcining the solid product.
[0011] Optionally, the iron source is selected from one or more of water-soluble iron salts; preferably, the iron source is selected from one or more of ferric chloride, ferric nitrate, ferric phosphate, ferrous chloride, ferrous nitrate, ferrous phosphate, ferrous sulfate, ferric iodide, ferric fluoride, ferric bromide and ferric sulfate;
[0012] The alumina is selected from one or more of α-type alumina powder, β-type alumina powder and γ-type alumina powder, preferably γ-type alumina powder; optionally, the particle size of the alumina powder is 0.5-50 μm;
[0013] The average particle size of the carbon quantum dots is 3-20 nm, preferably 5-15 nm, and the surface oxygen content is 10-40 wt%, preferably 15-30 wt%;
[0014] The aqueous ammonia is an aqueous solution of ammonia, and the concentration of the aqueous ammonia is 0.01-40 wt%, preferably 0.1-30 wt%, and further preferably 2-25 wt%.
[0015] Optionally, the weight ratio of the iron source: carbon quantum dots aqueous solution: alumina: aqueous ammonia is 1:(0.5-100):(5-500):(0.1-5); preferably 1:(5-50):(20-100):(0.2-3);
[0016] Optionally, the concentration of the carbon quantum dots in the carbon quantum dots aqueous solution is 100-10000 ppm, preferably 0.05-0.5 wt%.
[0017] Optionally, the mixing conditions in step S2 include mixing under stirring, mixing temperature is room temperature to 60°C, mixing time is 1-720 min; stirring speed is 20-2000 rpm;
[0018] In step S3, the calcination conditions include calcination temperature is 300-800°C, calcination time is 1-12 h; calcination atmosphere is air; preferably, the calcination temperature is 450-700°C, and the calcination time is 1-6 h.
[0019] The second aspect of the present disclosure provides a catalyst for preparing a nano-carbon material prepared by the method according to the first aspect of the present disclosure.
[0020] Optionally, the catalyst comprises alumina, and active metal oxides and carbon supported on the alumina; the metal element of the active metal oxides comprises iron;
[0021] Preferably, based on the total weight of the catalyst, the content of the active metal oxide is 0.1-10% by weight, the content of carbon is 0-1% by weight, and the content of alumina is 89-99.9% by weight; preferably, the content of the active metal oxide is 0.5-5% by weight, the content of carbon is 0-0.5% by weight, and the content of alumina is 94.5-99.5% by weight.
[0022] The catalyst has an average particle size of 0.1–100 μm; preferably 2–50 μm; and a BET specific surface area of 100–300 m². 2 / g, preferably 150-250m 2 / g.
[0023] The third aspect of this disclosure provides a method for preparing nano-carbon materials, comprising the following steps: contacting a carbon source with the catalyst described in the second aspect of this disclosure.
[0024] Optionally, the carbon source is selected from liquid hydrocarbons and gaseous hydrocarbons; the liquid hydrocarbons are selected from one or more hydrocarbon compounds with 5 to 20 carbon atoms; preferably, the liquid hydrocarbons are selected from one or more gasoline and diesel fuel.
[0025] The gaseous hydrocarbons are selected from one or more of alkanes having 1 to 4 carbon atoms, alkenes having 2 to 4 carbon atoms, and alkynes having 2 to 4 carbon atoms; preferably, they are selected from one or more of methane, ethane, propane, butane, ethylene, propylene, butene, butadiene, and acetylene.
[0026] Optionally, the contact reaction conditions include: a reaction temperature of 700–1000℃, a reaction pressure of 0–1MPa, and a contact reaction time of 5–3600s; preferably, the reaction temperature is 750–900℃, the reaction pressure is 0–0.2MPa, and the contact reaction time is 10–1200s.
[0027] The weight ratio of carbon source to catalyst is 1 to 100:1, preferably 5 to 50:1; or, the feed rate of gaseous hydrocarbons per gram of catalyst is 1 to 500 mL / min, preferably 5 to 100 mL / min; the feed rate of liquid hydrocarbons per gram of catalyst is 0.1 to 10 mL / min, preferably 0.5 to 5 mL / min.
[0028] This disclosure provides a fourth aspect of carbon nanomaterials prepared according to the method described in the third aspect of this disclosure;
[0029] The carbon content of the nanomaterial is 80% by weight or more, preferably 90% by weight or more, and more preferably 95% by weight or more; the BET specific surface area of the nanomaterial is 100–800 cm². 2 / g, preferably 200-600cm 2 / g; Optionally, the nano-carbon material includes carbon nanotubes, the carbon nanotubes having an average length of 0.2 to 500 μm and an average diameter of 0.5 to 100 nm; preferably, the average length is 1 to 100 μm and the average diameter is 2 to 50 nm.
[0030] Through the above technical solutions, this disclosure provides a catalyst and its synthesis method, as well as nano-carbon materials and their preparation method. Introducing carbon quantum dots into the catalyst preparation process can enhance the interaction between the active component iron and the supported alumina in the catalyst, improve and stabilize the dispersion of the active component iron on the supported alumina, and thus improve its catalytic performance. Using the catalyst of this disclosure in the preparation process of nano-carbon materials is simple, and the yield of nano-carbon materials is high, while the catalyst has high catalytic activity and long service life.
[0031] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Detailed Implementation
[0032] The following provides a detailed description of specific embodiments of this disclosure. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of this disclosure. The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values; these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0033] The first aspect of this disclosure provides a method for synthesizing a catalyst for preparing nano-carbon materials, comprising the following steps:
[0034] S1. Mix the iron source, carbon quantum dots, water and aluminum oxide to obtain a raw material mixture;
[0035] S2. The raw material mixture is mixed with ammonia water and reacted to obtain a solid product;
[0036] S3. The solid product is subjected to calcination treatment.
[0037] This disclosure provides a method for synthesizing a catalyst for preparing nano-carbon materials. By introducing carbon quantum dots into the catalyst preparation process, the interaction between the active component (iron) and the support (alumina) in the catalyst can be strengthened, and the dispersion of the active component iron on the alumina support can be improved and stabilized, thereby improving its catalytic performance. The catalyst of this disclosure is simple to use in the preparation process of nano-carbon materials, and the yield of nano-carbon materials is high, while the catalyst has high catalytic activity and long service life.
[0038] In one embodiment, the iron source is selected from one or more water-soluble iron salts; preferably, the iron source is selected from one or more of ferric chloride, ferric nitrate, ferric phosphate, ferrous chloride, ferrous nitrate, ferrous phosphate, ferrous sulfate, ferric iodide, ferric fluoride, ferric bromide, and ferric sulfate.
[0039] The alumina is selected from one or more of α-alumina powder, β-alumina powder and γ-alumina powder, preferably γ-alumina powder; optionally, the particle size of the alumina powder is 0.5-50 μm;
[0040] The average particle size of the carbon quantum dots is 3-20 nm, preferably 5-15 nm, and the surface oxygen content is 10-40% by weight, preferably 15-30% by weight.
[0041] The ammonia water refers to an aqueous solution of ammonia, and the concentration of ammonia water is generally 0.01 to 40% by weight, preferably 0.1 to 30% by weight, and more preferably 2 to 25% by weight.
[0042] In this disclosure, carbon quantum dots can be prepared by an electrochemical method, including: in an electrolytic cell, using graphite rods as anodes and cathodes, carrying out an electrochemical reaction in an electrolyte at 5-20V for 1-10 days to obtain a carbon quantum dot solution, wherein the concentration of carbon quantum dots in the carbon quantum dot solution is generally 100-10000ppm, preferably 0.05-0.5% by weight.
[0043] In one embodiment, the weight ratio of iron source: carbon quantum dot aqueous solution: alumina: ammonia is 1:(0.5-100):(5-500):(0.1-5); preferably 1:(5-50):(20-100):(0.2-3). The catalyst prepared according to the preferred ratio in this embodiment has superior catalytic performance and service life.
[0044] In one embodiment, the mixing conditions in step S2 include: mixing under stirring, mixing temperature from room temperature to 60°C, mixing time from 1 to 720 min, and stirring speed from 20 to 2000 rpm.
[0045] In one embodiment, in step S3, the calcination conditions include: a calcination temperature of 300–800°C and a calcination time of 1–12 h; and a calcination atmosphere of nitrogen or air. Preferably, the calcination temperature is 450–700°C and the calcination time is 1–6 h.
[0046] The second aspect of this disclosure provides a catalyst for preparing nano-carbon materials, prepared according to the method described in the first aspect of this disclosure.
[0047] In one embodiment, the catalyst comprises alumina and an active metal oxide and carbon supported on the alumina; the metal element of the active metal oxide includes iron.
[0048] The alumina is selected from one or more of alumina α-type alumina, β-type alumina and γ-type alumina, preferably γ-type alumina.
[0049] In a preferred embodiment, based on the total weight of the catalyst, the content of the active metal oxide is 0.1–10% by weight, the content of carbon is 0–1% by weight (the carbon content is not zero when the calcination atmosphere is nitrogen; the carbon content can be zero when the calcination atmosphere is air), and the content of alumina is 89–99.9% by weight; preferably, the content of the active metal oxide is 0.5–5% by weight, the content of carbon is 0–0.5% by weight, and the content of alumina is 94.5–99.5% by weight. Catalysts with compositions within the preferred range of this embodiment exhibit better performance.
[0050] In one embodiment, the catalyst has an average particle size of 0.1–100 μm; preferably 2–50 μm; and a BET specific surface area of 100–300 m². 2 / g, preferably 150-250m 2 / g.
[0051] A third aspect of this disclosure provides a method for preparing nano-carbon materials, comprising the following steps:
[0052] The carbon source is reacted with the catalyst described in the second aspect of this disclosure.
[0053] The method for preparing carbon nanomaterials disclosed herein can obtain higher yields of carbon nanomaterials.
[0054] In one embodiment, the carbon source is selected from liquid and gaseous hydrocarbons; the liquid hydrocarbons are selected from one or more hydrocarbon compounds with 5 to 20 carbon atoms; from the perspective of availability, the liquid hydrocarbons are preferably selected from one or more gasoline and diesel fuel.
[0055] The gaseous hydrocarbons are selected from one or more of alkanes having 1 to 4 carbon atoms, alkenes having 2 to 4 carbon atoms, and alkynes having 2 to 4 carbon atoms; preferably, they are selected from one or more of methane, ethane, propane, butane, ethylene, propylene, butene, butadiene, and acetylene. The method provided in this disclosure has broad applicability to raw materials.
[0056] In one embodiment, the contact reaction conditions include: a reaction temperature of 700–1000°C, a reaction pressure of 0–1 MPa, and a reaction time of 5–3600 s; preferably, the reaction temperature is 750–900°C, the reaction pressure is 0–0.2 MPa, and the reaction time is 10–1200 s. Here, the reaction time refers to the contact time between a specific reactant molecule and the catalyst, i.e., the time required for the reactant to contact the catalyst and transform into a product within the reactor. This is a microscopic concept, not a macroscopic concept of the total reaction time. Generally, the catalytic performance of a catalyst is expressed using the total macroscopic reaction time, such as 1–12 h.
[0057] The ratio of carbon source to catalyst can be expressed as the weight ratio of carbon source in contact with the catalyst to catalyst, or as the carbon source feed rate per unit mass of catalyst. Generally, the weight ratio of carbon source in contact with the catalyst to catalyst is 1–100:1, preferably 5–50:1. The feed rate per gram of catalyst is 1–500 mL / min for gaseous hydrocarbons, preferably 5–100 mL / min, and 0.1–10 mL / min for liquid hydrocarbons, preferably 0.5–5 mL / min. Following the preferred conditions provided in this embodiment, a superior reaction effect can be obtained. Optionally, when introducing gaseous hydrocarbons as a carbon source, nitrogen gas is introduced simultaneously with the gaseous hydrocarbons, and the nitrogen flow rate can be 0–1000 mL / min.
[0058] This disclosure provides a fourth aspect of carbon nanomaterials prepared according to the method described in the third aspect of this disclosure.
[0059] In one embodiment, the carbon content of the nano-carbon material is 80% by weight or more, preferably 90% by weight or more, and more preferably 95% by weight or more; the remaining components include elements such as oxygen, nitrogen, and hydrogen.
[0060] The BET specific surface area of the nano-carbon material is 100–800 cm². 2 / g, preferably 200-600cm 2 / g;
[0061] Optionally, the nanomaterial includes carbon nanotubes, the carbon nanotubes having an average length of 0.2 to 500 μm and an average diameter of 0.5 to 100 nm; preferably, the average length is 1 to 100 μm and the average diameter is 2 to 50 nm.
[0062] The nano-carbon material obtained in this disclosure has a yield that is more than twice that of the catalyst, preferably more than five times, and even more preferably more than ten times. The yield can represent the performance of the catalyst to a certain extent, especially its lifetime; the higher the yield, the longer the lifetime of the catalyst.
[0063] The present disclosure is further described in detail below through examples. All raw materials used in the examples are commercially available.
[0064] Particle size was determined by transmission electron microscopy (TEM), specifically by TecnaiG at FEI GmbH in the Netherlands. 2 Obtained using an F20S-TWIN transmission electron microscope, accelerating voltage 20kV;
[0065] The specific surface area of the sample was determined by analyzing the low-temperature adsorption curve of N2 using a 3H-2000PSX physical adsorption instrument from Best Instrument Technology (Beijing) Co., Ltd.
[0066] The component contents of the product were determined by XPS and XRF, respectively. The XPS instrument was a PHI Quantera SXM (Scanning X-ray Microprobe), using a monochromator, an Al anode target, an energy resolution of 0.5 eV, and a chamber vacuum of 6.7 × 10⁻⁶. -8 Pa. Sputtering conditions: Scanning Ar + Gun, area 1×1mm 2 The sputtering rate was 20 nm / min, and the emission current was 20 mA. XRF was performed using a Rigaku Electric Co., Ltd. 3271E X-ray fluorescence spectrometer for semi-quantitative determination of the elemental composition of the samples. The sample was prepared by powder compression; after sample processing, a certain amount of sample was taken, ground in a mortar to <300 mesh, and then compressed into tablets.
[0067] Example 1
[0068] a. At room temperature and pressure, add 1000L of distilled water to the electrolytic cell. At the same time, connect the positive and negative electrodes of the DC power supply to the two ends of the graphite rod and place it vertically into the cell. Adjust the voltage to 10V and start timing. After stirring and reacting for 5 days, a carbon quantum dot solution is obtained. The average particle size of the carbon quantum dots is 9nm, the surface oxygen content is 23% by weight, and the concentration of the carbon quantum dot solution is 0.02% by weight.
[0069] b. Stir 20g of ferric nitrate with an appropriate amount of carbon quantum dot solution at room temperature and pressure for 1 hour to obtain the first mixture.
[0070] c. Add an appropriate amount of γ-type alumina micro powder to the first mixture and continue stirring for 2 hours to obtain the second mixture;
[0071] d. Add ammonia water (concentration of 25% by weight) dropwise to the second mixture, continue stirring for 1 hour, dry and then calcine at 500℃ for 4 hours.
[0072] The catalyst was obtained and denoted as A1.
[0073] The proportions of the above reactants are as follows: the weight ratio of iron source: carbon quantum dot aqueous solution: alumina powder: ammonia is 1:25:20:3.
[0074] Comparative Example 1
[0075] This comparative example follows the method of Example 1, but differs from Example 1 in that the same weight of water is used instead of the aqueous solution of carbon quantum dots to obtain a catalyst, denoted as DB1.
[0076] Comparative Example 2
[0077] This comparative example uses the method of Example 1, but differs from Example 1 in that:
[0078] A catalyst, denoted as DB2, was obtained by replacing the aqueous solution of carbon quantum dots with an oxidized graphite ink solution of the same weight and concentration.
[0079] Example 2
[0080] This embodiment follows the method of Example 1, except that the weight ratio of iron source: carbon quantum dot aqueous solution: alumina micropowder: ammonia water is 1:5:40:5. The resulting catalyst is denoted as A2.
[0081] Example 3
[0082] This embodiment follows the method of Embodiment 1, but differs from Embodiment 1 in that the weight ratio of iron source: carbon quantum dot aqueous solution: alumina micro powder: ammonia is 1:150:20:30, and the ammonia concentration is 2.5% by weight. The resulting catalyst is denoted as A3.
[0083] Example 4
[0084] This embodiment follows the method of Embodiment 1, but differs from Embodiment 1 in that: in step d, the calcination temperature is 850°C and the calcination time is 12 hours. The resulting catalyst is denoted as A4.
[0085] The component content and structural parameter data of the catalysts prepared by the above examples and comparative examples are listed in Table 1 below.
[0086] Table 1
[0087]
[0088] The following reaction examples are used to illustrate the catalytic effect of the catalysts prepared in the examples and comparative examples in the preparation method of carbon nanomaterials.
[0089] Reaction Example 1
[0090] An appropriate amount (1.5 g) of the catalyst obtained in the above examples and comparative examples was placed in a ceramic boat, which was then placed in the middle of a tube furnace. After replacing the air in the tube with nitrogen, the temperature was raised to 760°C with continuous nitrogen flow. When the temperature reached 760°C and the pressure reached 0.2 MPa, acetylene was introduced and the time was started. The time required for the reactants to contact the catalyst and convert into products in the reactor was 36 s. After 6 hours of reaction, the acetylene flow was stopped and the heating was stopped. After the temperature dropped below 100°C, the nitrogen flow was stopped, and the ceramic boat was removed. The mass of the material in the boat before and after the reaction was weighed, and the weight difference was obtained as the mass of the obtained nano-carbon material. The nitrogen flow rate was 50 mL / min, and the acetylene flow rate was 30 mL / min (the feed rate of gaseous hydrocarbons per gram of catalyst was 20 mL / min). The test results are listed in Table 2 below.
[0091] Reaction Example 2
[0092] Referring to the method in Reaction Example 1, the difference from Reaction Example 1 is:
[0093] The reaction temperature was 850℃, the reaction pressure was 0.5MPa, the acetylene flow rate was 50mL / min (the feed rate of gaseous hydrocarbons per gram of catalyst was 33.3mL / min), and the time required for the reactants to contact the catalyst and convert into products in the reactor was 20s; the rest of the process was the same as in Example 1. The test results are listed in Table 2 below.
[0094] Reaction Example 3
[0095] This reaction example uses liquid hydrocarbons as the carbon source, specifically catalytic diesel (from Tianjin Petrochemical). The reaction process includes a reaction temperature of 800℃, a reaction pressure of 0.2 MPa, a liquid hydrocarbon feed rate of 2 mL / min (the feed rate of liquid hydrocarbons per gram of catalyst is 1.33 mL / min), and a reaction time of 63 s for the reactants to contact the catalyst and convert into products within the reactor. The test results are listed in Table 2 below.
[0096] Table 2
[0097]
[0098] The yield growth rate of nano-carbon materials is calculated as follows: (mass of nano-carbon materials in 6 hours - mass of nano-carbon materials in 1 hour) / mass of nano-carbon materials in 1 hour × 100%.
[0099] According to the data in Table 2 above:
[0100] Compared with the catalyst prepared in Example 1 (without adding carbon quantum dot aqueous solution), the catalyst prepared in Example 1 according to the method provided in this disclosure can obtain more nano-carbon materials and a higher nano-carbon material yield growth rate under the same reaction time, and has better catalytic activity and service life.
[0101] In Comparative Example 2, an oxidized graphite ink solution was added to replace the aqueous solution of carbon quantum dots. Compared with Comparative Example 2, the catalyst prepared in Example 1 according to the method provided in this disclosure can obtain more nano-carbon materials and a higher yield growth rate of nano-carbon materials under the same reaction time, and has better catalytic activity and service life.
[0102] Comparing Example 2 and Example 3, in Example 2, the catalyst was prepared according to the optimized raw material ratio provided in this disclosure, which is "the weight ratio of iron source: carbon quantum dot aqueous solution: alumina: ammonia is 1:(0.5~100):(5~500):(0.1~5)". The raw material ratio in Example 3 is not within this optimized range. The catalyst prepared in Example 2 can obtain more nano-carbon materials and a higher nano-carbon material yield growth rate under the same reaction time, and has better catalytic activity and service life.
[0103] Furthermore, comparing Example 2 with Example 1, in Example 1 the catalyst was prepared according to the more preferred raw material ratio range of "1:(5-50):(20-100):(0.2-3)" provided in this disclosure. Compared with the catalyst prepared in Example 2, the catalyst prepared in Example 1 can obtain more nano-carbon materials and a higher nano-carbon material yield growth rate under the same reaction time, and has better catalytic activity and service life.
[0104] Comparing Example 1 with Example 4, Example 1 was prepared according to the optimized reaction conditions provided in this disclosure. The catalyst obtained in Example 1 can produce more nano-carbon materials and a higher yield rate of nano-carbon materials under the same reaction time, and has better catalytic activity and service life.
[0105] Comparing Reaction Example 1 (using Al catalyst) with Reaction Example 2, where Reaction Example 1 was prepared according to the preferred reaction conditions provided in this disclosure, the growth rate of the carbon nanomaterials in Reaction Example 1 was higher.
[0106] The carbon content and structural characteristics of the carbon nanomaterial products (carbon nanotubes) prepared after 6 hours of reaction in the above reaction example 1 are listed in Table 3 below.
[0107] Table 3
[0108]
[0109] As can be seen from the data in Table 3 above, the carbon content of the nanomaterials obtained by using the catalyst provided in this disclosure is higher.
[0110] The preferred embodiments of this disclosure have been described in detail above. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.
[0111] It should also be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.
[0112] Furthermore, various different embodiments of this disclosure can be combined in any way, as long as they do not violate the spirit of this disclosure, they should also be regarded as the content disclosed in this disclosure.
Claims
1. A method for synthesizing a catalyst for preparing nano-carbon materials, characterized in that, Includes the following steps: S1. Mix the iron source, carbon quantum dot aqueous solution and alumina to obtain a raw material mixture; S2. The raw material mixture is mixed with ammonia water and reacted to obtain a solid product; S3. The solid product is subjected to calcination treatment.
2. The synthesis method according to claim 1, characterized in that, The iron source is selected from one or more water-soluble iron salts; preferably, the iron source is selected from one or more of ferric chloride, ferric nitrate, ferric phosphate, ferrous chloride, ferrous nitrate, ferrous phosphate, ferrous sulfate, ferric iodide, ferric fluoride, ferric bromide and ferric sulfate. The alumina is selected from one or more of α-alumina powder, β-alumina powder and γ-alumina powder, preferably γ-alumina powder; optionally, the particle size of the alumina powder is 0.5-50 μm; The average particle size of the carbon quantum dots is 3-20 nm, preferably 5-15 nm; the surface oxygen content of the carbon quantum dots is 10-40% by weight, preferably 15-30% by weight. The ammonia solution is an aqueous solution of ammonia, and the concentration of the ammonia solution is 0.01 to 40% by weight, preferably 0.1 to 30% by weight, and more preferably 2 to 25% by weight.
3. The synthesis method according to claim 1, characterized in that, The weight ratio of iron source: carbon quantum dot aqueous solution: alumina: ammonia is 1:(0.5~100):(5~500):(0.1~5); preferably 1:(5~50):(20~100):(0.2~3); Optionally, the concentration of carbon quantum dots in the aqueous solution is 100–10000 ppm, preferably 0.05–0.5% by weight.
4. The synthesis method according to claim 1, characterized in that, The conditions for the mixing reaction in step S2 include: mixing under stirring, mixing temperature from room temperature to 60°C, mixing time from 1 to 720 min, and stirring speed from 20 to 2000 rpm; In step S3, the conditions for the calcination treatment include: a calcination temperature of 300–800°C and a calcination time of 1–12 h; and a calcination atmosphere of air. Preferably, the calcination temperature is 450–700°C and the calcination time is 1–6 h.
5. The catalyst for preparing nano-carbon materials prepared by the method according to any one of claims 1 to 4.
6. The catalyst according to claim 5, characterized in that, The catalyst comprises alumina, an active metal oxide supported on the alumina, and carbon; the metal element of the active metal oxide includes iron. Preferably, based on the total weight of the catalyst, the content of the active metal oxide is 0.1-10% by weight, the content of carbon is 0-1% by weight, and the content of alumina is 89-99.9% by weight; preferably, the content of the active metal oxide is 0.5-5% by weight, the content of carbon is 0-0.5% by weight, and the content of alumina is 94.5-99.5% by weight. The catalyst has an average particle size of 0.1–100 μm; preferably 2–50 μm; and a BET specific surface area of 100–300 m². 2 / g, preferably 150-250m 2 / g.
7. A method for preparing nano-carbon materials, characterized in that, Includes the following steps: The carbon source is reacted with the catalyst described in claim 5 or 6.
8. The method according to claim 7, characterized in that, The carbon source is selected from liquid hydrocarbons and gaseous hydrocarbons; the liquid hydrocarbons are selected from one or more hydrocarbon compounds with 5 to 20 carbon atoms; preferably, the liquid hydrocarbons are selected from one or more gasoline and diesel fuel. The gaseous hydrocarbons are selected from one or more of alkanes having 1 to 4 carbon atoms, alkenes having 2 to 4 carbon atoms, and alkynes having 2 to 4 carbon atoms; preferably, they are selected from one or more of methane, ethane, propane, butane, ethylene, propylene, butene, butadiene, and acetylene.
9. The method according to claim 8, characterized in that, The conditions for the contact reaction include: a reaction temperature of 700–1000°C, a reaction pressure of 0–1 MPa, and a contact reaction time of 5–3600 s; preferably, the reaction temperature is 750–900°C, the reaction pressure is 0–0.2 MPa, and the contact reaction time is 10–1200 s. The weight ratio of carbon source to catalyst is 1 to 100:1, preferably 5 to 50:1; or, the feed rate of gaseous hydrocarbons per gram of catalyst is 1 to 500 mL / min, preferably 5 to 100 mL / min; the feed rate of liquid hydrocarbons per gram of catalyst is 0.1 to 10 mL / min, preferably 0.5 to 5 mL / min.
10. The nano-carbon material prepared by the method according to any one of claims 7 to 9; wherein the carbon content of the nano-carbon material is 80% by weight or more, preferably 90% by weight or more, more preferably 95% by weight or more; and the BET specific surface area of the nano-carbon material is 100 to 800 cm². 2 / g, preferably 200-600cm 2 / g; Optionally, the nano-carbon material includes carbon nanotubes, the carbon nanotubes having an average length of 0.2 to 500 μm and an average diameter of 0.5 to 100 nm; preferably, the average length is 1 to 100 μm and the average diameter is 2 to 50 nm.